2021
DOI: 10.31234/osf.io/gzu3y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Media Browsing and Adolescent Well-Being: Challenging the “Passive Social Media Use Hypothesis”

Abstract: A recurring hypothesis in the literature is that “passive” social media use (browsing) leads to negative effects on well-being. This preregistered study investigated a rival hypothesis, which states that the effects of browsing on well-being depend on person-specific susceptibilities to envy, inspiration, and enjoyment. We conducted a three-week experience sampling study among 353 adolescents (13-15 years, 126 assessments per adolescent). Using a novel, N=1 method of analysis, we found sizeable heterogeneity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…Thus, our findings do not support the claim that PSMU is reliably to blame for the harmful effects of social media use. Consistent with this, Valkenburg et al (2021) propose that the effects of social media may also depend on personspecific variables, including susceptibility to envy, inspiration, and enjoyment. Such person-to-person differences may be obscured by examining a dataset in the aggregate.…”
Section: Discussionmentioning
confidence: 75%
“…Thus, our findings do not support the claim that PSMU is reliably to blame for the harmful effects of social media use. Consistent with this, Valkenburg et al (2021) propose that the effects of social media may also depend on personspecific variables, including susceptibility to envy, inspiration, and enjoyment. Such person-to-person differences may be obscured by examining a dataset in the aggregate.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, recent studies that have adopted an idiographic (i.e., N = 1 or person-specific) media effects paradigm [56] have found that a small group of adolescents experienced negative effects of SMU on well-being (around 10-15%) and another small group experienced positive effects (also around 10%-15%). Reassuringly though, most adolescents experienced no or negligible effects [57].…”
Section: Understanding Inconsistent Interpretationsmentioning
confidence: 97%
“…Indeed, the meta-analytic results for social comparison yielded consistent moderate associations of social comparison with lower levels of aggregated well-being and life-satisfaction [14] and higher levels of depression [16]. In this vein, it must be noted that 77.5% of SM users report never feeling worse after comparing themselves to other users within a period of two weeks [41], only a minority of SM users feel envious while using SM [42], that they more often feel enjoyment [43], and can also get inspired from SM-induced social comparisons [44].…”
Section: Social Comparisonmentioning
confidence: 90%